Pembentukan Karakter Peserta Didik Melalui Pembelajaran Sastra Berbasis Literasi Digital - Asriani Thahir; Sri Wahyuni (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The aims of this research are: To describe how the Character Building of Students through Digital Literacy-Based Literature Learning. This research is a descriptive qualitative research. Data collection is done by using literature study techniques, documentation, interviews, observations, and tests. The results of this study indicate that literary learning in the form of fairy tales and digital-based fables plays a significant role in the formation of students' character. Students seem to animate and are able to understand the moral messages contained in the story well, through the characters contained in the story, students can get valuable learning and begin to implement it in their daily lives both at home and at school. The values that exist in digital literacy-based literary learning, such as being able to build the character of fourth grade students at MIS Fathul Munir, Ternate City, become polite, responsible, disciplined, cooperative, confident, thorough, and caring or responsive to the problems that exist in the community.